PERAN KELEMBAGAAN PETANI DALAM MENURUNKAN INEFISIENSI PRODUKSI USAHATANI SAWI PAKCOY - Rasidin Karo Karo Sitepu; Veralianta Br Sebayang; Uding Sastrawan (Journal of Integrated Agribusiness, 2022)
The formation of farmer institutions generally aims to increase access to capital, production facilities, markets, adoption of innovations and agricultural information. The existence of farmer institutions also makes it easier for the government and stakeholders to facilitate farmers. Farmer institutions are important to increase farmers' access to agricultural capital and information. This study aims to determine the role of farmer institutions in reducing production technical inefficiency. The research location is in Cianjur Regency, West Java Province in 2020. The number of respondents is 100 farmers, who were selected using the purposive method. Production inefficiency analysis using stochastic frontier processed with SAS@9.4 software. The results showed that the dominant factors influencing farmers' production were land area, and the use of labor. Farmer institutions have a role in reducing technical inefficiency, but it is not significant. Assistance to farmer groups should continue to be carried out by the government, to increase the role of farmer groups in improving the welfare of farmers.